2019
DOI: 10.1039/c9fo00287a
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the chemical and bioactive properties of Hibiscus sabdariffa L. calyces from Guinea-Bissau (West Africa)

Abstract: Hibiscus sabdariffa L. exhibited beneficial properties and represents a promising species for food applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 38 publications
(31 reference statements)
1
33
0
4
Order By: Relevance
“…Concerning the five species found at Bandim market, the use of leaves, fruits and flowers of Adansonia digitata, Amaranthus hybridus, Hibiscus sabdariffa and Sesamum radiatum is reported in West Africa and elsewhere, and their composition and dietary characteristics have been analyzed by several authors [9,10,12,33,34,35,36,37,38]. Bombax costatum is also referenced in some studies, but the compositional data is only available for flowers and young fruits [12,39,40,41].…”
Section: Discussionmentioning
confidence: 99%
“…Concerning the five species found at Bandim market, the use of leaves, fruits and flowers of Adansonia digitata, Amaranthus hybridus, Hibiscus sabdariffa and Sesamum radiatum is reported in West Africa and elsewhere, and their composition and dietary characteristics have been analyzed by several authors [9,10,12,33,34,35,36,37,38]. Bombax costatum is also referenced in some studies, but the compositional data is only available for flowers and young fruits [12,39,40,41].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have been reported on the various constituents of different plant parts like flowers, leaves, stem, root, bark, seeds of Hibiscus sabdariffa Linn. [22,[26][27][28][29].…”
Section: Constituents Of Hibiscus Sabdariffamentioning
confidence: 99%
“…The inflammatory activities were ascribed to the phenolic compounds, especially the flavonoids (gossypetin, hibiscetin, quercetin, and sabdaretin), in the extract. Similarly, [102] ascribed the potent anti-inflammatory effects of HS extracts to the phenolic acids, especially trans 3-O-caffeoylquinic acid. However, in an earlier study, [103] documented that HS extract performed poorly when compared to aqueous extracts of Acacia nilotica in the inhibiting (reduction of paw oedema) effect on a carrageenan-induced paw.…”
Section: Anti-inflammatory Effectsmentioning
confidence: 99%
“…The authors concluded that extracts of HS were effective at all tested concentrations in inhibiting the growth of bacteria, and thus could be used as a source of bioactive compounds as well as a biocidal agent. Recently, [102] showed the biocidal activities of HS extracts (hydroethanolic and infusion extracts) on various important bacterial and fungal species. They found a higher minimum inhibitory concentration (MICs) against Micrococcus flavus, S. aureus, Listeria monocytogenes, P. aeruginosa, and Salmonella typhimirium in both extracts.…”
Section: Biocidal Activitiesmentioning
confidence: 99%
See 1 more Smart Citation